Food safety in the seafood industry : a practical guide for ISO 22000 and FSSC 22000 implementation - Soares, Nuno, 1975-; Martins, Cristina, 1990-; Vicente, António A. (Chichester, UK ; Hoboken, NJ : Wiley Blackwell, 2016)
Seafood is one of the most traded commodities worldwide. It is thus imperative that all companies and official control agencies ensure seafood safety and quality throughout the supply chain. Written in an accessible and succinct style, Food Safety in Seafood Industry: A practical guide for ISO 22000 and FSSC 22000 implementation brings together in one volume key information for those wanting to implement ISO 22000 or FSSC 22000 in the seafood manufacturing industry. Concise and highly practical, this book comprises: a presentation of seafood industry and its future perspectives the description of the main hazards associated to seafood (including an annexe featuring the analysis of notifications related with such hazards published by Rapid Alert System for Food and Feed - RASFF) interpretation of ISO 22000 clauses together with practical examples adapted to the seafood manufacturing industry the presentation of the most recent food safety scheme FSSC 22000 and the interpretation of the additional clauses that this scheme introduces when compared to ISO 22000 This practical guide is a valuable resource for seafood industry quality managers, food technologists, managers, consultants, professors and students.
Fishery sector -- Food safety -- The EN ISO 22000:2005 -- Food safety management system EN ISO 22000:2005 -- The FSSC 22000 certification.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Seafood industry -- Quality control; Seafood industry -- Safety measures; Seafood -- Quality control; Seafood -- Safety measures; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Seafood industry -- Quality control; Seafood industry -- Safety measures; Seafood -- Quality control; Seafood -- Safety measures; Electronic books; Electronic books